End-crosslinking of controlled telechelic poly(N-isopropylacrylamide) toward a homogeneous gel network with photo-induced self-healing - Ida, Shohei; Kimura, Ryohei; Tanimoto, Satoshi; Hirokawa, Yoshitsugu (Polymer journal, 2017)
Telechelic poly( N -isopropylacrylamide) (PNIPAAm) was designed to prepare homogeneous and self-healable gels by end-crosslinking. The PNIPAAm with carboxyl groups at both polymer ends and trithiocarbonate (TTC) in the main chain was obtained by reversible addition-fragmentation chain transfer (RAFT) polymerization of NIPAAm with a symmetric TTC compound (CTA-1) as a RAFT agent. The obtained polymers of a series of molecular weights were well-defined within a narrow molecular weight distribution ( M w / M n ~1.1). Then, the end groups of the resultant PNIPAAms were quantitatively transformed into activated esters as reactive sites for gelation. These designed PNIPAAms were employed for an end-crosslinking reaction with trifunctional amine crosslinker, and it was found that gelation condition was closely related to the molecular weight and the concentration of the telechelic prepolymers. Furthermore, the obtained gel showed the characteristic ultraviolet-induced self-healing owing to the chain exchange reaction of TTC groups. Self-healable gel was designed by end-crosslinking of controlled telechelic polymer carrying a trithiocarbonate group in the middle of the chain. The prepolymers, which were precisely synthesized by RAFT polymerization, were crosslinked with branched crosslinker using activated ester chemistry to produce the network with same molecular weight network chain between crosslinking points. The obtained gel showed UV-induced self-healing owing to the function of the trithiocarbonate groups.